2011
DOI: 10.1111/j.1365-2044.2011.06704.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of propofol or desflurane on postoperative cognitive dysfunction in patients undergoing coronary artery bypass surgery*

Abstract: SummaryWe investigated the influence of either propofol or desflurane on the incidence of postoperative cognitive dysfunction in a randomised trial of 180 patients undergoing coronary artery bypass surgery. The primary outcome was incidence of postoperative cognitive dysfunction at 3 months, defined as ‡ 1 SD deterioration in two or more of 12 neurocognitive tests. Secondary outcomes included early postoperative cognitive dysfunction (between days three and seven), delirium on day one, morbidity and length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 31 publications
3
91
0
4
Order By: Relevance
“…44,45 Preliminary human data suggest that inhalational anesthetics may be associated with better short-term cognitive performance after on-pump CABG surgery. 46,47 In contrast, the incidence of delirium did not differ between the desflurane and propofol groups. 46 In the present trial, we also did not detect an influence of the volatile anesthetic sevoflurane on the incidence of delirium.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…44,45 Preliminary human data suggest that inhalational anesthetics may be associated with better short-term cognitive performance after on-pump CABG surgery. 46,47 In contrast, the incidence of delirium did not differ between the desflurane and propofol groups. 46 In the present trial, we also did not detect an influence of the volatile anesthetic sevoflurane on the incidence of delirium.…”
Section: Discussionmentioning
confidence: 78%
“…46,47 In contrast, the incidence of delirium did not differ between the desflurane and propofol groups. 46 In the present trial, we also did not detect an influence of the volatile anesthetic sevoflurane on the incidence of delirium.…”
Section: Discussionmentioning
confidence: 78%
“…9 We assumed that the incidence of POCD could be as high as 30% in the sevoflurane group and 10% in the propofol group. 22 Considering a 20% difference in incidence to be clinically significant, 144 patients would be needed to achieve a statistical power of 0.8 with a type I error of 0.05. To compensate for withdrawals, 148 patients were enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, deeper isoflurane anaesthesia titrated to the bispectral index (BIS) also results in better postoperative information processing [73]. Furthermore, two recent studies comparing propofol with sevoflurane [46] and desflurane [74] found a higher incidence of cognitive dysfunction in patients after propofol-based anaesthesia. These results suggest that there might even be a protective effect of inhalational anaesthesia, possibly mediated by so-called anaesthetic pre-and post-ischaemic conditioning.…”
Section: Possible Causes Of Pocd Related To Anaesthesiamentioning
confidence: 99%